Extraction of Natural Dyes from Babadotan Leaves (Ageratum conyzoides L.) using Ultrasound-Assisted Extraction Method and Its Utilization in Fabric Dying - Amalia Rahmawati; Harjono Harjono (Indonesian Journal of Chemical Science, 2023)
Natural dyes are used as an alternative to synthetic dyes which have a negative impact on human health and the environment. Plants that can be applied as natural dyes are babadotan weed. In this study, extraction of natural dyes from babadotan leaves was carried out using the UAE method. Identification of compounds contained in dyes using UV-Vis instruments, FTIR, phytochemical tests, and total tannin and flavonoid tests. The yield test on the extracted extract showed that 70% ethanol extract produced the highest value when compared to other samples. The results of the phytochemical test showed that the three extract samples positively contained tannins, while the flavonoid phytochemical test showed that the aquadest extract positively contained flavonoids. The results of the FTIR instrument test show that the three extract samples produce functional groups contained in tannin compounds. The test results of the UV-Vis spectrophotometer instrument indicated the possibility of a C=O chromophore. The total tannin content test showed that the 70% ethanol viscous extract showed the highest value, while the total flavonoid content test showed that the aquadest viscous extract showed the highest value. Dyeing fabrics treated with FeSO4 mordant showed more intense color results when compared to fabrics treated with other mordant. Stability test of dyed fabrics against washing with detergent and drying in direct sunlight for 6 hours showed good color fastness.